LEARNING OUTCOMES ALIGNED WITH THAI QUALIFICATIONS FRAMEWORK FOR HIGHER EDUCATION IN NURSING STUDENTS - Thanaphakawatkul, Chonkanok; Isarangura Na Ayudhaya, Phitinan; Pusopa, Chuleeporn (International Online Journal of Education and Teaching, 2023)
This study aimed to investigate how students view their own learning outcomes in line with Thai Qualifications Framework for Higher Education (TQF: H.Ed.) as well as the relationship between learning outcomes and academic achievement. Participating in the study were 151 BSN students in their year who completed a learning outcomes questionnaire and indicated academic achievement. According to the data, the course successfully high-level learning outcomes. The highest average score was the moral and ethics domain, while the lowest average score was the knowledge domain. There was no statistically insignificant in the relationship between learning outcomes regarding higher education qualification standards based on student’s perceptions and academic achievement. The findings can use as a guideline for developing of teaching and learning evaluation. The teaching technique should focus on active learning and encourage students to learn and achieve learning outcomes and academic achievement. The findings can serve as a course syllabus for enhancing the evaluation of education. Active learning should be emphasized to motivate student to learn and improve their academic performance.